A General and Specific Utility-Based Adaptive Routing for Delay Tolerant Networks. (20th January 2014) - You, Lei; Li, Jianbo; Wei, Changjiang; Dai, Chenqu; Xu, Jixing
Abstract : The nonexistence of an end-to-end path poses great challenges in directly adapting the traditional routing algorithms for ad hoc or mobile ad hoc networks (MANETs) to delay tolerant networks (DTNs). In this paper, an adaptive routing protocol that makes use of both self-aware and destination-aware utility metrics to evaluate the potential throughput between every pair of nodes is proposed. We theoretically analyze the nodes' spraying process and discover the relationship between the initial number of copies and the latency of the message distribution process, by which we can further control the expected latency under a certain level. Compared with Epidemic, Spray And Wait Spray, And Focus and Encounter-based routing, our proposed algorithm is the only one that achieves comparable performance under both Helsinki City Scenario and Cambridge-iMote Scenario.